A universal, rapid method for clean transfer of nanostructures onto various substrates - Li, Hai (2014)
Transfer and integration of nanostructures onto target substrates is the prerequisite for their fundamental studies and practical applications. Conventional transfer techniques that involve stamping, lift-off, and/or striping suffer from the process-specific drawbacks, such as the requirement for chemical etchant or high-temperature annealing and the introduction of surface discontinuities and/or contaminations that can greatly hinder the properties and functions of the transferred materials. Herein, we report a universal and rapid transfer method implementable at mild conditions. Nanostructures with various dimensionalities (i.e., nanoparticles, nanowires, and nanosheets) and surface properties (i.e., hydrophilic and hydrophobic) can be easily transferred to diverse substrates including hydrophilic, hydrophobic, and flexible surfaces with good fidelity. Importantly, our method ensures the rapid and clean transfer of two-dimensional materials and allows for the facile fabrication of vertical heterostructures with various compositions used for electronic devices. We believe that our method can facilitate the development of nanoelectronics by accelerating the clean transfer and integration of low-dimensional materials into multidimensional structures.